Tacit Knowledge and Product Information about the Environmental Impact towards the Purchase Intention of Electric Motorcycles - Pramajaya, Agung; Haryanto, Jony Oktavian (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2021)
In recent years, Indonesia has started to adopt electric motorcycles (EMCs), but until 2019 the market share of electric vehicles (EVs) was only around 0.05%. This figure is far from the target set by the Ministry of Industry of a 20% market share in 2025. This quantitative research was conducted to get a novel picture of what potential customers think about EMC products. The proposed model used structural equation modelling with SmartPLS-3 over 300 respondents. The research found that detailed product information positively and significantly influences consumer attitudes toward adopting EMCs. Tacit knowledge also positively and significantly influences consumer attitudes toward the environment. Furthermore, tacit knowledge directly affects the purchase intention of EMCs with a significant and positive value. As the mediating variable, consumer attitudes towards the environment have no mediation effect toward purchase intention. These findings are expected to increase the public’s knowledge and awareness of the environmental impact in determining which EMC products are more environmentally friendly than others. Here, environmentally friendly means the absence of direct emissions on vehicle exhaust and the total direct and indirect emissions.